Long-term, therapy-related visual outcome of 49 cases with retinal arterial macroaneurysm: a case series and literature review. Issue 10 (16th April 2015) - Koinzer, Stefan; Heckmann, Jan; Tode, Jan; Roider, Johann
Abstract : Purpose: Retinal arterial macroaneurysms (RAMAs) are acquired dilations of branches of the central retinal artery. Treatment depends on vision-limiting complications. We compare the long-term visual acuity (VA) in three groups according to treatment. Methods: 49 charts of patients with RAMA were reviewed. 16 remained untreated, 15 received photocoagulation and 18 vitrectomy. Patients underwent full ophthalmological examinations and up-to-date imaging. We evaluated chosen therapy, complications and final VA at the last visit. Results: 65% of the cohort was female, aged 75±11 years (mean±SD). Follow-up was 34±23 months. These parameters did not differ significantly between the three groups. In the observed group, initial VA was 0.48 (mean log MAR) vs 0.35 at the final visit, in the photocoagulation group 0.55 vs 0.59, and in the vitrectomy group 1.8 vs 0.77. VA was significantly worse at enrolment in the vitrectomy group, while all other VA differences were not significant. Conclusions: The overall visual prognosis of RAMA was good, even after macular complications. VA remained unchanged in the observed and the laser groups and was comparable in all groups after 3 years. Based on an individual treatment decision, all therapies were effective and efficient. If subfoveal haemorrhage caused a macular hole, the VA outcome was limited.